New Brillouin fiber laser configuration with high output power - Shirazi, M.R.; Harun, Sulaiman Wadi; Thambiratnam, K.; Biglary, Mozhgun; Ahmad, Harith (John Wiley & Sons, 2007)
A new Brillouin fiber laser (BFL) configuration is demonstrated using similar components as a conventional BFL. The BFL is configured so that the single-mode fiber receives more Brillouin pump (BP) power to generate higher back-propagating Stokes power and Brillouin gain in the cavity. The proposed configuration shows an output peak power of -0.5 dBm, which is 5.7 dB higher when compared with the conventional configuration. However, the maximum output power was observed at 0.5 dBm with an output coupler of 20 to 80 ratio, whereby 20% of the light is allowed to oscillate in the cavity and 80% of the light is coupled out as output. The linewidth of the BFL (whose BP linewidth is about 200 MHz) is measured to be ∼30 kHz, using a heterodyne beat technique.